2021
DOI: 10.36941/jesr-2021-0088
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mindfulness Training Program on the Impulsivity Among Students with Learning Disabilities

Abstract: In recent years, many studies showed positive effects of implementing mindfulness practices according to some cognitive and psychical well-being measurements among many participants; especially, adolescents and adults. Few studies appeared on the effectiveness of mindfulness practices for students with learning disabilities. Therefore, this study aimed to assess the effectiveness of mindfulness training programs on the impulsivity levels for participants with learning disabilities in inclusive elementary schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 60 publications
(88 reference statements)
1
4
0
Order By: Relevance
“…And these results can be attributed to the fact that TOH task requires following a set of rules and instructions so that students can perform successfully on it, and it has levels that range in difficulty from the easy to the more difficult level, and we have followed the appropriate gradation with them, and this attracts them to perform effectively on the task, which had the best effect in reducing their impulsiveness. The results of this study are consistent with the results of some other studies, which concluded that the training programs (including those on CT) are effective in reducing impulsivity and improving attentional control (for example, Alqarni & Hammad, 2021;Chambers et al, 2008;Franco et al, 2016;Ghahramaniet al, 2016;Munoz-Olano & Hurtado-Parrado, 2017;Peckham & Johnson, 2018;Rivera-Flores, 2015;Shafiee-Kandjani et al, 2017;Torto-Seidu et al, 2021;Wass et al, 2011Wass et al, , 2012. In contrast, the results of the current study differed with the results of some studies, for example, the study of Karimi Goodarzi et al (2018) concluded that there was no significant difference in hyperactivity/impulsivity between the experimental group (the group to which CT was applied) and control group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…And these results can be attributed to the fact that TOH task requires following a set of rules and instructions so that students can perform successfully on it, and it has levels that range in difficulty from the easy to the more difficult level, and we have followed the appropriate gradation with them, and this attracts them to perform effectively on the task, which had the best effect in reducing their impulsiveness. The results of this study are consistent with the results of some other studies, which concluded that the training programs (including those on CT) are effective in reducing impulsivity and improving attentional control (for example, Alqarni & Hammad, 2021;Chambers et al, 2008;Franco et al, 2016;Ghahramaniet al, 2016;Munoz-Olano & Hurtado-Parrado, 2017;Peckham & Johnson, 2018;Rivera-Flores, 2015;Shafiee-Kandjani et al, 2017;Torto-Seidu et al, 2021;Wass et al, 2011Wass et al, , 2012. In contrast, the results of the current study differed with the results of some studies, for example, the study of Karimi Goodarzi et al (2018) concluded that there was no significant difference in hyperactivity/impulsivity between the experimental group (the group to which CT was applied) and control group.…”
Section: Discussionsupporting
confidence: 91%
“…The findings offered early evidence in favor of the effectiveness of cognitive modelling training as a strategy for reducing impulsivity in students. The results of the study of Alqarni and Hammad (2021) indicated that a mindfulness training program significantly reduced impulsivity in the experimental group of participants with learning difficulties. By looking at the theoretical frameworks and previous studies related to the variables of the current study, namely (CT, impulsivity, and attentional control), the following becomes clear :…”
Section: Impulsivitymentioning
confidence: 95%
“…The numerous academic failures are the reason why students with learning difficulties do not believe that all the effort they make will serve to improve their performance or that they will be successful in their school tasks [33]. Recent studies based on mindfulness have shown a significant reduction in impulsivity in students with learning difficulties [34], the possibility of improvement in the regulation of attention, thoughts and emotions through breathing techniques in the face of behavioral problems [35] as well as the decrease in levels of hyperactivity and inattention in students with Attention Deficit Hyperactivity Disorder [36].…”
Section: Discussionmentioning
confidence: 99%
“…According to Linz and Sturm (2013), individuals with severe disabilities have a lower level of social integration compared to people with other types of disabilities, and accordingly, they have greater difficulties with developing interpersonal skills. Individuals with other types of disabilities, such as sensory and mental disabilities, may also require special training programs that may be largely unavailable (DePauw and Gavron, 2005;Shapiro et al, 2012;Alqarni and Hammad, 2021).…”
Section: Journal Of Disability Research 2024mentioning
confidence: 99%
“…The United Nations' standard principles on equal opportunities for persons with disabilities and the International Convention on the Rights of Persons with Disabilities (Grandisson et al, 2012;Hammad and Awed, 2020), for example, have pointed out that persons with disabilities have a fundamental right to participate in sports activities (Weston, 2017). People with disabilities are most affected by stigma, and due to their different physical structures or mental states, they experience social isolation, rejection, and ostracism, which intensifies their frustration in social interactions, leading to the emergence of individual social withdrawal behavior and the formation of collective subcultures (Albrecht et al, 2019;Alqarni and Hammad, 2021;Awed and Hammad, 2022).…”
Section: Introductionmentioning
confidence: 99%